As narrativas enquadradas n'As Afinidades Eletivas de Goethe - Cipriani, Ieda Maria Caricari (2012)
Elective Affinities (Die Wahlverwandtschaften, 1809) by Johann Wolfgang von Goethe is an imbricated novel, elaborated by symbols repeated throughout the narrative, which build a complex and organized structure. The essential element for the organization of this novel is inserted narratives: Ottilie's diary, the tableaus and the novel Die Wunderlichen Nachbarskinder , which constitute the main narrative. The objective of this doctoral thesis is to analyze how these inserted narratives are grafted in the novel, what is the relationship between the main narrative and inserted narratives and how they work in the novel. The study is done as a Close Reading, that finds significant interrelationships of the main narrative in the inserted narratives and vice versa. The theories of Barthes and Bachelard provide a fresh look at the Goethean work and were used as theoretical foundation of this thesis.